2013
DOI: 10.1159/000350323
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Reproductive Effects of the <b><i>Vgf</i></b>-Derived Peptide TLQP-21 in Female Rats: In vivo and in vitro Studies

Abstract: Background: VGF (non-acronymic), a protein expressed in the hypothalamus and pituitary, is involved in the control of metabolism and body weight homeostasis. Different active peptide fragments are generated from VGF, including TLQP-21. Previous studies of our group reported that this molecule participates also in the regulation of reproductive function in male rats, with predominant stimulatory effects. Methods: We report herein a series of studies on the reproductive effects of TLQP-21 in female rats, as eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
(79 reference statements)
1
23
1
Order By: Relevance
“…Interestingly, like CHO-K1 cells, O-342 cells are of ovarian origin, suggesting a potential novel role of TLQP-21 in reproduction. This appears to be consistent with a recent publication reporting TLQP-21 effects on reproduction in female rats (33).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, like CHO-K1 cells, O-342 cells are of ovarian origin, suggesting a potential novel role of TLQP-21 in reproduction. This appears to be consistent with a recent publication reporting TLQP-21 effects on reproduction in female rats (33).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we have recently demonstrated TLQP-21 binding sites on CHO cells through the use of Atomic Force Microscopy (Cassina et al, 2013). Interestingly, the rat ovary express high levels of TLQP-21, which has been proposed to affect female reproduction by modulating pituitary LH release (Aguilar et al, 2013; Noli et al, 2014) The statistical distribution of the attractive force between TLQP-21 and its binding site is indicative of a single class of binding sites. This presence of a TLQP-21 binding site in these cells is consistent with their unique dose- and time-dependent increases of intracellular calcium (Ca 2+ ) mobilization in response to TLQP-21 (Cassina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The best studied fragment is the C-terminal internal peptide designated TLQP-21, whose sequence and function we have identified and extensively characterized (Bartolomucci et al, 2006). TLQP-21 is a multifunctional peptide that regulates energy balance (Bartolomucci et al, 2006, Jethwa et al, 2007, Possenti et al, 2012), glucose metabolism (Stephens et al, 2012), gastric function (Severini et al, 2009), nociception (Rizzi et al, 2007, Chen et al, 2013, Fairbanks et al, 2014), blood pressure regulation (Fargali et al, 2014), reproduction (Aguilar et al, 2013) and stress (Razzoli et al, 2012). Importantly, it was found that a central infusion of TLQP-21 increases energy expenditure and prevents obesity in rodents (Bartolomucci et al, 2006, Jethwa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%